Ratio Decidendie Judges On The Cancellation Of Certificate Of Land Right That Does Not Remove The Ownership In Kendari State Court (Case Study On Decision No. 62 / Pdt.G / 2012 / PN.Kdi) - Muh. Ramli Jaya; Akhmad Khisni (Jurnal Akta, 2020)
This study aims to determine how the Ratio Decidendie judges and legal consequences of the implementation of verdict on cancellation of certificate of ownership that does not remove the right to land ownership in the State Court of Kendari. This study uses the type of normative juridical research using law approach, conceptual approach and the approach the case with premier legal materials, secondary and tertiary material.Based on the studies concluded that the judges verdict in case number 62 / Pdt.G / 2012 / Pn.Kdi confirming ownership of the Plaintiff. Certificate Revocation Proprietary No. 37 / Anduonuhu Village and property rights certificate No. 38 / Anduonuhu Village through Decision Kendari State Administrative Court No. 29 / G / 2010 / PTUN-Kdi flawed due to its publication of juridical / procedural defect. While consideration by the State Court case number 62 / Pdt.G / 2012 / Pn.Kdi explain pedestal of land rights in the form of Decree of the Governor of the Province of South East Celebes Number. 11 / HM / 1979 dated January 16, 1979 not been declared void. So that the Plaintiff's legal rights remain attached. Plaintiffs can reapply for the certificate issued by the applicable legislation.Keywords: Ratio Decidendie; Certificate Revocation Property Rights; Land Rights.